The Yogyakarta City Government's Policy in Realizing an Inclusive City for People with Disabilities - Danik Ummu Izzah; Muhammad Eko Atmojo (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
The digest of the findings of this article aims to analyze the implementation of inclusion policies for people with disabilities in Yogyakarta City, in accordance with Law Number 8 of 2016 and Regional Regulation Number 4 of 2019, using Merilee S. Grindle's theory which emphasizes the alignment between policy content and implementation context. The method used is a qualitative case study approach applied by collecting data through field observations, and in-depth interviews with relevant Regional Apparatus Organizations (OPD). The results show that despite various initiatives, such as the establishment of the Inclusive Kemantren Forum (FKI) and the development of disability- friendly infrastructure, challenges are still faced in cross-sector coordination and the availability of accessible public facilities. Therefore, increased synergy between the government, private sector and communities is deemed necessary to ensure effective policy implementation. In conclusion, although progress has been made in building an inclusive city, continuous improvements in regulations, infrastructure, and public participation are still needed to achieve optimal inclusivity for people with disabilities in Yogyakarta City.